Kesehatan Mental Guru dalam Dinamika Lingkungan Kerja dan Manajemen Stres - Nofitasari, Nofitasari; Sofiyah, Siti; Noviana, Irma; Silmia, Ami; Wibowo, Ryzna Dwi Anitania; Putri, Desy Elisya; Ghufron, M. Nur (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2025)
Teacher mental health is an essential aspect of education, particularly at the Elementary School/Madrasah Ibtidaiyah (SD/MI) level. An unsupportive work environment and ineffective stress management can reduce teacher performance and negatively impact the quality of learning. This study employed a quantitative approach with proportionalrandom sampling to select 120 MI/SD teachers in Kudus Regency as the sample. The research instruments consisted of a work environment scale, a stress management scale, and a mental health scale. Data were analyzed using multiple linear regression with the assistance of SPSS software. The findings revealed that the quality of the work environment and stress management significantly influence teachers’ mental health, both simultaneously and partially (p < 0.05). The coefficient of determination (R²) of 0.616 indicates that these two independent variables contribute 61.6% to the variation in teachers’ mental health. These results confirm that a supportive work environment and effective stress management skills are key factors in maintaining teachers’ mental well-being. This aligns with occupational well-being theories that highlight the importance of psychosocial factors in supporting teacher performance. Schools, madrasahs, and policymakers are advised to optimize workplace facilities, create a conducive work climate, and provide regular stress management training. Such efforts can enhance teachers’ mental well-being, thereby supporting the delivery of high-quality and sustainable learning.